Confidences of a Spec-Writer - Douglas Darden (Oz, 1992)
This article contains the diary letters qua letters left me by a man whom, according to the expression he often used himself, we called the Spec-writer, or with a certain trepidation, the Specter. Whether these letters need any introductory remarks may be open to question.